上唇に発生した孤立性線維性腫瘍の1例 - 清水, 英孝; 藤田, 源太郎; 今井, 智章; 道澤, 雅裕 (日本口腔外科学会雑誌, 2010)
In the WHO classification of soft tissue tumors, solitary fibrous tumor (SFT) belongs to fibroblastic/myofibroblastic tumors with intermediate malignancy (rarely metastasizing). Although this tumor occurs mainly in the pleura, extrapleuratic tumors have been reported in ubiquitous sites, including the oral cavity, with a predisposition to the buccal region. We report a rare SFT arising in the upper lip. A 70-year-old man presented with a painless mass. MR images showed a homogeneously enhanced neoplasm. The tumor was resected surgically and exhibited the histopathological features of SFT. It consisted of collagen-forming, CD34-positive fibroblastic spindle cells in a haphazard arrangement, accompanied by a prominent hemangiopericytoma-like branching vascular pattern. Although there was no evidence of local recurrence or metastasis 1 year after sugery, long-term follow-up is mandatory because of the unpredictable behavior of SFT.